Center for Extended Services: A Land Grant Concept - Eddy J. Van Meter (Educational Considerations, 1975)
The goal of the Center for Extended Services is to provide assistance to local school personnel in their own environment. Services provided by the Center include educational facilities evaluation, curriculum planning, administration improvement, and grant proposal preparation.